2020
DOI: 10.1007/s10049-020-00807-3
|View full text |Cite
|
Sign up to set email alerts
|

Role of lung ultrasonography in the diagnosis of COVID-19 patients admitted to the emergency department

Abstract: Introduction In this study, the use of lung ultrasonography (LUS) to diagnosis lung findings was evaluated in patients with suspected COVID-19 who were admitted to the emergency department (ED). Methods This observational clinical study was conducted in the ED of the Ankara City Hospital during the period April 1–30, 2020. Patients who were admitted to the ED were triaged as COVID-19 infected and who agreed to undergo LUS/LCT (lung computed tomography) were included in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 13 publications
1
10
0
Order By: Relevance
“…Despite a larger average score in COVID-19, our data showed that the total LUSS score was not significantly different between COVID-19 patients and controls when using RT-PCR as the reference test. The modest diagnostic performance we observed corresponds with what Şan et al [21] had reported (62.5% sensitivity and specificity). Raiteri et al [22] used the relatively similar intensive care unit LUS scoring system and reported low sensitivity (66.7%) but slightly better specificity (85.6%).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Despite a larger average score in COVID-19, our data showed that the total LUSS score was not significantly different between COVID-19 patients and controls when using RT-PCR as the reference test. The modest diagnostic performance we observed corresponds with what Şan et al [21] had reported (62.5% sensitivity and specificity). Raiteri et al [22] used the relatively similar intensive care unit LUS scoring system and reported low sensitivity (66.7%) but slightly better specificity (85.6%).…”
Section: Discussionsupporting
confidence: 91%
“…The diagnostic performance discrepancy noticeable in the LUS in COVID-19 literature can be explained by the varying definitions of LUS outcome measure (i.e., how to interpret the images). Some studies have merely used any presence of B-lines or consolidations indicative of COVID-19 [21,25,27,32]. Others developed an arbitrary LUS scoring system based on a 5-point Likert scale [24] or a 6-point system [28].…”
Section: Discussionmentioning
confidence: 99%
“…Our study identified nine studies comparing LUS with CT for the diagnosis of interstitial pneumonia caused by COVID-19 [8][9][10][11][12][13][14][15][16]. In four out of five cases the diagnoses done by LUS and CT were in agreement.…”
Section: Principal Findingsmentioning
confidence: 85%
“…A total of 1896 documents were retrieved. After reading the titles, abstracts, and full text of the documents, nine articles were included in the analysis [8][9][10][11][12][13][14][15][16] (Figure 1).…”
Section: Literature Selection Processmentioning
confidence: 99%
“… 2 Although most patients experience mild disease, 14% of patients have lung involvement. 3 , 4 As a result, lung imaging is pivotal in every recommendation for guiding the diagnosis and management of COVID‐19 patients. 1 , 5 …”
mentioning
confidence: 99%